PENGARUH GDP DAN NILAI TUKAR NEGARA MITRA DAGANG TERHADAP EKSPOR KARET INDONESIA - Nico Andriantoni; Wahyu Hidayat; Zainal Arifin (Jurnal Ilmu Ekonomi, 2020)
International trade is one of the economic activities that plays an important role for a country. The benefits of international trade are related to economic growth, national development and national welfare. The condition of limited resources is no longer a barrier to meeting the needs of a country with exchange and trade. Rubber is one of the leading export commodities for the Indonesian plantation sector. Indonesia is one of the main producers of natural rubber number two in the world after Thailand. The purpose of this study was to determine the effect of Gross Domestic Product and the exchange rate of trading partner countries on Indonesian Rubber exports. The type of data used is panel data of Indonesia Rubber export partner countries in 2009-2018. The method used is panel data regression. The results showed that the export of Indonesian Rubber with Gross Domestic Product was positive and significant. And the exchange rate also has a positive and significant effect